The effectiveness of using image media on beginning word writing skills in grade 1 elementary school students during COVID-19 pandemic - Nirwana, Lina Ayu (CV. Mitra Palupi, 2021)
Background: Writing is an activity that cannot be kept away from teaching and learning activities in schools. Writing activities can make students be active and develop in learning activities and can stimulate the existence of stringing skills and composing words.Purpose: The research aims to investigate the effectiveness of the image media in increasing the writing skills of the first grader of elementary.Design and methods: The research applied case study methods with descriptive analysis techniques. Samples in this study were taken from SDN Cibinong 01 with a population of 20 grade 1 students consisting of 10 male students and 10 female students.Results: The results obtained from the study showed that the effectiveness of the image media used to hone the initial writing skills of grade 1 students at SDN Cibinong 01 as a whole can be said to have been good with a percentage of 85%. This shows the effectiveness of the use of image media is effective enough to be used to hone the initial word writing skills in grade 1 elementary school students during the pandemic.